Prosody Drives Structure: The Case of Compounds in Akan - Marfo , Charles (Issues in Language Studies, 2016)
This paper discusses compound constructions in Akan, which are mostly nouns. Compounding is generally explained as a morphosyntactic word-formation process and the resulting compound word is commonly described as a “new” linguistic unit (Haspelmath, 2002; Marfo, 2009). The paper focuses on Noun-Noun (N-N) and Noun-Adjective (N-Adj) compounds in Akan and particularly contends that, for N-N and N-Adj compounds to be realized in Akan, the compound members should map into one prosodic phrase. It is also suggested that the same mapping should be the case if there could be proper or consistent realization of some phonological changes that occur in the compound. In this direction, the paper explains that the syntactic structure of the compound (i.e., the noun phrase (NP)), does not solely ensure the domain of the Akan compound nor the domain properties that trigger the rules that apply in it, but phonological information as well; thus, prosodic constraints are observed. Furthermore, the structure of the Akan compound is illuminated in terms of Attribute-Value Matrix (e.g., Butt & King, 1998). The paper reiterates in conclusion that compounds in Akan and rules that apply in them are better accounted for through dictates of the prosodic structure.